1982
DOI: 10.1111/j.1476-5381.1982.tb08772.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ethanol on Inhibitory and Motor Responses in the Rat and Rabbit Anococcygeus and the Bovine Retractor Penis Muscles

Abstract: Ethanol (200 mm) reduced the response to inhibitory nerve stimulation in the rat and rabbit anococcygeus and the bovine retractor penis (BRP) muscles. Ethanol also reduced the response to the inhibitory extract from the BRP consistent with the inhibitory factor in these extracts playing some part in the response to inhibitory nerve stimulation. Ethanol's effect on the response to other inhibitory stimuli was examined in the rabbit anococcygeus and the BRP. In the anococcygeus the response to carbachol was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
2
11
0
Order By: Relevance
“…Both these effects are produced by other agents that inhibit nitrergic nerve-stimulation-induced relaxations, such as NO synthase inhibitors, haemoglobin and methylene blue (Rand, 1992a), and are attributable to removal of a NO-mediated relaxant influence. However, ethanol also reduced the contractile action of noradrenaline (Gillespie et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both these effects are produced by other agents that inhibit nitrergic nerve-stimulation-induced relaxations, such as NO synthase inhibitors, haemoglobin and methylene blue (Rand, 1992a), and are attributable to removal of a NO-mediated relaxant influence. However, ethanol also reduced the contractile action of noradrenaline (Gillespie et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, effects other than interaction with NO may also be involved in the actions produced by alcohols, especially at the relatively high concentrations used, since the tone of the muscle was decreased by all the alcohols except ethanol. It is possible that this reduction in tone is due to disordering of the cell membrane by the alcohols, causing a reduction of the intracellular calcium concentration in the smooth muscle cells, as suggested by Gillespie et al (1982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temperature was maintained at 35±1 °C, and the pH was adjusted to 7.2-7. 4. Drugs were applied to the tissue by changing the inflow to the organ bath from normal Krebs solution to Krebs containing the appropriate drug, without alteration of flow rate.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that ethanol increases the spontaneous noradrenaline release from the rat vas deferens (1), but it decreases the stimulated release of noradrenaline from the rabbit cardiac sympathetic nerves (2,3). Recently, Gillespie et al (4) have shown that ethanol reduces the motor response to adrenergic nerve stimulation in the rat anococcygeus muscle. Despite these apparent effects on the adrenergic systems, there have been little electrophysiological data on the direct cellular effects of ethanol.…”
mentioning
confidence: 99%